Clinicopathological features of IgG4-related disease complicated with orbital involvement. Issue 3 (May 2014) - Hagiya, Chihiro; Tsuboi, Hiroto; Yokosawa, Masahiro; Hagiwara, Shinya; Hirota, Tomoya; Takai, Chinatsu; Asashima, Hiromitsu; Miki, Haruka; Umeda, Naoto; Horikoshi, Masanobu; Kondo, Yuya; Sugihara, Makoto; et al.
Abstract Objective. IgG4-related disease (IgG4-RD) is characterized by IgG4-positive plasmacytic infiltration and fibrosis in various organs. Orbital involvement in IgG4-RD includes lacrimal glands, extra-ocular muscles, trigeminal nerve and other parts of the orbit. Immunohistochemical staining is used to diagnose IgG4-RD in patients with orbital inflammation. The purpose of this retrospective study was to clarify the clinicopathological features of IgG4-RD complicated with orbital involvement. Methods. We examined the clinical features, pathological findings and response to treatment in nine patients with IgG4-RD who underwent orbital tissue biopsy between April 2010 and August 2012 at the University of Tsukuba Hospital. Results. Among the nine patients, eight had dacryoadenitis, one had infraorbital nerve swelling, and another one had IgG4-related orbital inflammation. Involvement of other organs was identified in all patients, including involvement of the salivary glands, lymph nodes, lung, kidney and para-aorta. In all patients, biopsy samples from orbital tissues showed lymphoplasmacytic infiltration and fibrosis, and IgG4-positive/IgG-positive plasmacyte ratio of > 40%. All patients were treated with prednisolone (0.6 mg/kg/day) and responded well in early phase, although relapse was noted in two patients following tapering of prednisolone, evident by swelling of lacrimal glands. Conclusion. Patients with IgG4-RD complicated with orbital involvement often present with involvement of other organs. The histopathological findings of orbital tissue match the characteristic features of IgG4-RD. Corticosteroid is effective for orbital and systemic involvement in IgG4-RD.